Is the Financing of German Health and Long-Term Care Insurance Sustainable? - Friedrich Breyer; Normann Lorenz (Wirtschaftsdienst)
Abstract Based on a recent non-parametric estimation of the relationship between age, lifespan and health and long-term care expenditures in German social health insurance, we present a simulation of the future development of contribution rates in the two branches of the German social security system. Depending on different assumptions of the future growth of GDP per worker, our estimates show that by 2040 the total social security contribution rate could reach between slightly below 50 % and above 53 % of gross wages. Thus the sustainability of the German social security system is severely jeopardised.